Hockey and coach education: perspectives of Aboriginal coaches from Manitoba's Interlake region - Sirant, Michael P. (2010)
Focusing on the perspectives of coaches from a First Nations community in Manitoba’s Interlake region, the purpose of this study was to understand the importance of hockey in the community and to explore needs/interests in relation to coaching education. Of specific interest with respect to coaching education was the identification of content and delivery elements that would optimize the relevance of such initiatives to the needs and interests of the selected community. Grounded in a qualitative tradition, a case study design was employed using individual interviews with Aboriginal youth hockey coaches to collect the data required for achieving the purpose of the study. The findings revealed that the coaches viewed hockey as a critical means for positively altering behavioral patterns and attitudes of children. The findings also make clear the need for sport organizations to use their resources to deliver ongoing coaching education tailored to the needs of the selected community. October 2010